The Influence of Halal Labels on Rachmat Bread Sales in Bungursari District, Purwakarta - Ahmad Ali Sopian (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
Prohibition of consuming food which is prohibited encourages every Muslim to be more selective in choosing products to be consumed. Halal labels can be a benchmark for choosing products before making a purchase in accordance with Islamic syari'ah which is protected by consumer protection laws. Halal labels for Muslim consumers are a guarantee of being protected from consuming non-halal food, medicine and cosmetics. For producers, halal labels can provide benefits, namely increasing competitiveness, consumer confidence, turnover of production and sales. This research was conducted using descriptive quantitative method, using data collection through observation, interviews, questionnaires and documentation. Determination of the number of samples used in this study was determined by the Probability Sampling technique using Simple Random Sampling. This aims to determine the effect of Halal Label on the sale of Roti Rachmat in Bungursari District Purwakarta and to find out how much influence the Halal Label has on the company's sales turnover. The results of this study indicate that the halal label has a significant effect on the sale of Rachmat Bread. This can be seen from the results of the regression test, namely the value of the coefficient of determination (R Square) of 0.542 from the correlation value / relationship (R) 0.743. So that the independent variable (halal label) gives effect to the dependent variable (Sales) of 54.2%, the remaining 43.2% is influenced by other factors not examined in this study.